Biologic therapies and bone loss in rheumatoid arthritis. Issue 2 (February 2017) - Zerbini, C.; Clark, P.; Mendez-Sanchez, L.; Pereira, R.; Messina, O.; Uña, C.; Adachi, J.; Lems, W.; Cooper, C.; Lane, N.
Abstract Introduction Rheumatoid arthritis (RA) is a common systemic autoimmune disease of unknown cause, characterized by a chronic, symmetric, and progressive inflammatory polyarthritis. One of the most deleterious effects induced by the chronic inflammation of RA is bone loss. During the last 15 years, the better knowledge of the cytokine network involved in RA allowed the development of potent inhibitors of the inflammatory process classified as biological DMARDs. These new drugs are very effective in the inhibition of inflammation, but there are only few studies regarding their role in bone protection. The principal aim of this review was to show the evidence of the principal biologic therapies and bone loss in RA, focusing on their effects on bone mineral density, bone turnover markers, and fragility fractures. Methods Using the PICOST methodology, two coauthors (PC, LM-S) conducted the search using the following MESH terms: rheumatoid arthritis, osteoporosis, clinical trials, TNF- antagonists, infliximab, adalimumab, etanercept, certolizumab, golimumab, IL-6 antagonists, IL-1 antagonists, abatacept, tocilizumab, rituximab, bone mineral density, bone markers, and fractures. The search was conducted electronically and manually from the following databases: Medline and Science Direct. The search period included articles from 2003 to 2015. The selection included only original adult human research written in English. Titles were retrieved and the same two authors independently selected the relevant studies for a full text. The retrieved selected studies were also reviewed completing the search for relevant articles. The first search included 904 titles from which 253 titles were selected. The agreement on the selection among researchers resulted in a Kappa statistic of 0.95 (p < 0.000). Only 248 abstracts evaluated were included in the acronym PICOST. The final selection included only 28 studies, derived from the systematic search. Additionally, a manual search in the bibliography of the selected articles was made and included into the text and into the section of "small molecules of new agents." Conclusion Treatment with biologic drugs is associated with the decrease in bone loss. Studies with anti-TNF blocking agents show preservation or increase in spine and hip BMD and also a better profile of bone markers. Most of these studies were performed with infliximab. Only three epidemiological studies analyzed the effect on fractures after anti-TNF blocking agent's treatment. IL-6 blocking agents also showed improvement in localized bone loss not seen with anti-TNF agents. There are a few studies with rituximab and abatacept. Although several studies reported favorable actions of biologic therapies on bone protection, there are still unmet needs for studies regarding their actions on the risk of bone fractures.